Carbon material doped titanium-based tin antimony nickel composite coating electrode and preparation method and application thereof
The preparation of carbon material-doped titanium-based tin antimony-nickel composite coating electrodes was solved by pulse electrodeposition, which solved the problems of short service life of Ni-Sb-SnO2 electrode and low ozone concentration, and achieved the effect of electrolyzed water to prepare high-efficiency ozone and electrodes Improvement of lifespan.
Patent Information
- Application Number
- CN202411320284.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing Ni-Sb-SnO2 electrodes for preparing ozone by electrolyzing water have a short service life, which limits its widespread use in industrial applications. The ozone concentration generated by the traditional corona discharge method is low, which increases production costs.
The titanium-based tin antimony-nickel composite coating electrode doped with carbon material was prepared by pulse electrodeposition. The density and active sites of the electrode were improved through multiple quenching operations, the coating thickness and surface roughness were increased, and the electrocatalytic performance was improved.
It significantly extends the service life of the electrode, improves the efficiency and ozone concentration of electrolyzed water to prepare ozone, reduces production costs, and provides electrocatalytic materials with more industrial application potential.
Smart Images

Figure CN119287411A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a carbon material-doped titanium-based tin-antimony-nickel composite coating electrode and a preparation method and application thereof. Background Art
[0002] Ozone is a strong oxidant, widely used in sterilization, chemical synthesis, wastewater treatment and other aspects. In industry, ozone is generally prepared by corona discharge. However, the ozone concentration produced by this method is low, usually only 1% to 3%. In order to obtain pure ozone, additional equipment and expenses are required to separate pure oxygen from the air, which undoubtedly increases the production cost. In addition, during the high-voltage ionization process, a small amount of nitrogen oxides (NO x ), which has been proven to have carcinogenic risks. In recent years, electrochemical ozone production through water electrolysis has attracted widespread attention due to its simple operation and simple equipment.
[0003] At present, the anode materials for preparing ozone by electrolysis of water mainly include PbO 2 、Ni-Sb-SnO 2 and boron-doped diamond (BDD). However, due to the EU's implementation of the RoHS directive, PbO 2 The use of BDD materials in electrical and electronic equipment is strictly restricted. In addition, although BDD materials have excellent performance, their high price and high reaction potential restrict their industrial application. 2 The electrode is considered to be a promising option due to its easy preparation, high oxygen evolution overpotential, low cost and excellent electrocatalytic performance. However, its short service life has become the main bottleneck restricting its industrial application. Therefore, solving this problem is crucial to promote the development of Ni-Sb-SnO 2 The widespread application of electrodes in industrial fields is crucial. Summary of the invention
[0004] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a carbon material doped titanium-based tin-antimony-nickel composite coating electrode and its preparation method and application. The present invention adopts simple and low-cost pulse electrodeposition to prepare a carbon material and antimony co-doped tin oxide intermediate layer. The introduction of carbon material increases the thickness and surface roughness of the electrode coating and introduces a large number of active sites. Subsequently, through multiple quenching operations, the electrode surface is made denser and thicker. These designs significantly improve the electrocatalytic performance and service life of the electrode.
[0005] The technical solution adopted by the present invention is as follows:
[0006] The method for preparing a carbon material-doped titanium-based tin-antimony-nickel composite coating electrode comprises the following steps:
[0007] 1) Titanium sheet pretreatment: The titanium sheet is subjected to surface grinding, alkali washing and acid treatment in sequence;
[0008] 2) Preparation of active intermediate layer: placing the titanium sheet treated in step 1) in an electrodeposition solution for constant temperature pulse electrodeposition, wherein the electrodeposition solution is a mixture containing a tin source, an antimony source and a carbon material powder, drying after electrodeposition, and then calcining in a muffle furnace to grow an intermediate layer doped with a carbon material on the titanium sheet;
[0009] 3) Cyclic thermal oxidation and quenching treatment: Step 2) After the sintered titanium sheet is taken out of the muffle furnace, it is immediately immersed in a quenching liquid containing a tin source, an antimony source and a nickel source while it is hot for quenching treatment, and then placed in a high-temperature muffle furnace for sintering again for thermal oxidation treatment. The above quenching and thermal oxidation steps are repeated for multiple cycles to obtain a titanium-based tin-antimony-nickel metal oxide composite coating electrode.
[0010] Furthermore, the alkali washing process in step 1) is: degreasing in a 10-40wt% sodium hydroxide solution for 30-90min, the temperature of the solution is controlled between 50-100°C, and then the residual alkali solution on the surface is rinsed with deionized water; the acid washing process is: etching in a 10-40wt% oxalic acid solution for 60-120min, the temperature of the solution is controlled between 50-100°C, and then the residual acid solution on the surface is rinsed with deionized water.
[0011] Furthermore, the preparation process of the electrodeposition solution in step 2) is as follows: choline chloride and ethylene glycol are mixed, the molar ratio of choline chloride to ethylene glycol is 1:1-10, heated and stirred in a constant temperature oil bath until a colorless solution is formed, the oil bath temperature range is 50-100°C, and then a tin source, an antimony source and a carbon material are added to the solution, and stirred to form a uniform dispersion.
[0012] Furthermore, in the step 2) electrodeposition solution, the tin source is at least one of tin tetrachloride, stannous oxalate, and stannous chloride, the antimony source is antimony trichloride, and the carbon material powder is at least one of carbon fiber, diamond, graphene, conductive carbon black, and carbon nanotubes.
[0013] Furthermore, in the electrodeposition solution of step 2), the concentration of the tin source is 0.1-1M, the concentration of antimony trichloride is 0.01-0.1M, and the concentration of the carbon material is 0.1-1g / L.
[0014] Furthermore, the electrodeposition in step 2) adopts a three-electrode system, the treated titanium sheet is used as the cathode, and two anodes with an area larger than the titanium sheet are placed in parallel on both sides of the cathode, and the cathode and the anode are immersed in the electrodeposition liquid for pulse electrodeposition reaction, and the anode can be at least one of a graphite electrode, a platinum sheet electrode, and an iridium tantalum titanium electrode. The size area of the anode is 1.2-3.5 times the size area of the cathode.
[0015] Furthermore, the average current density of the pulse electrodeposition in step 2) is 5-50 mA / cm 2 , preferably 10-25 mA / cm 2 , the frequency is 0.1-100HZ, preferably 5-20HZ, the duty cycle is 10-90%, preferably 40-60%, the deposition temperature is 50-100℃, preferably 60-90℃, and the electrodeposition time is 10-40min, preferably 20-40min.
[0016] Further, in step 2), after the pulse electrodeposition is completed, the titanium sheet is placed in an oven for drying and then placed in a muffle furnace for calcination. The oven drying temperature is 80-160°C, preferably 100-140°C, the drying time is 5-10h, the muffle furnace calcination temperature is 400-700°C, preferably 450-600°C, and the calcination time is 1-5h.
[0017] Furthermore, in step 3), the quenching liquid uses isopropanol as a solvent, the tin source concentration in the quenching liquid is 0.1-1M, the antimony source concentration is 0.01-0.1M, the nickel source concentration is 1-10mM, the tin source is at least one of tin tetrachloride, stannous oxalate, and stannous chloride, the antimony source is antimony trichloride, and the nickel source is at least one of nickel chloride, nickel acetate, nickel sulfate, and nickel carbonate.
[0018] Furthermore, in step 3) of the cyclic thermal oxidation and quenching process, the roasting temperature range of the muffle furnace is 400-700°C, preferably 450-600°C. After roasting for 5-20 minutes, the titanium sheet is taken out of the muffle furnace and immediately placed in the quenching liquid for cooling, and then roasted again after soaking for 0.5-2 minutes. The above steps are repeated 5-15 times, and the roasting time in the muffle furnace is extended to 1-5 hours after the last soaking in the quenching liquid.
[0019] The present invention also discloses the application of the carbon material doped titanium-based tin antimony nickel composite coating electrode in the electrochemical preparation of ozone, adopts a double electrode system, carries out the reaction in an electrolytic cell, the electrolyte is a 0.01-0.1M sulfuric acid aqueous solution, the carbon material doped titanium-based tin antimony nickel composite coating electrode is used as the anode, and the platinum electrode is used as the cathode, and the electrocatalytic ozone preparation reaction is carried out.
[0020] The electrode of the present invention can also be well used in the electrocatalytic degradation of organic pollutants, with the carbon material-doped titanium-based tin-antimony-nickel composite coating electrode as the anode, the stainless steel sheet as the cathode, the electrolyte being a 0.01-0.1M sodium sulfate aqueous solution, the electrolyte containing organic pollutants, and the electrocatalytic degradation reaction of the organic pollutants.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) The present invention uses non-noble metal salt as raw material, obtains an intermediate layer through pulse electrodeposition and roasting, and then prepares a tin-antimony-nickel composite coating electrode through a multiple quenching process. The preparation method is simple and low in cost.
[0023] 2) The oxide intermediate layer introduced in the present invention can change the morphology and crystallinity of the electrode, enhance the adhesion between the active layer and the titanium substrate, and thus extend the service life of the electrode.
[0024] 3) The present invention adds carbon material to the metal oxide coating, increases the coating thickness and surface roughness, and provides abundant active sites. In addition, the multiple quenching operation steps will leave a large number of defects on the electrode surface. The increase of active sites and defects can enhance the catalytic activity of the catalyst, thereby improving the efficiency of preparing ozone by electrolyzing water. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A front scanning electron microscope schematic diagram of the carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 1 at 100 μm;
[0026] Figure 2 A schematic diagram of a side scanning electron microscope at 100 μm of a carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 1;
[0027] Figure 3 A front scanning electron microscope schematic diagram of the carbon fiber-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 2 at 100 μm;
[0028] Figure 4 A schematic diagram of a side scanning electron microscope at 100 μm of a carbon fiber-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 2;
[0029] Figure 5 A front scanning electron microscope schematic diagram of the conductive carbon black-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 3 at 100 μm;
[0030] Figure 6 A schematic diagram of a side scanning electron microscope at 100 μm of a conductive carbon black-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 3;
[0031] Figure 7 A front scanning electron microscope schematic diagram of the diamond-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 4 at 100 μm;
[0032] Figure 8 A schematic diagram of a side scanning electron microscope at 100 μm of a diamond-doped titanium-based tin-antimony-nickel composite coating electrode prepared in Example 4;
[0033] Fig. 9 A schematic diagram of a front scanning electron microscope at 100 μm for an undoped titanium-based tin-antimony-nickel composite coating electrode prepared in Comparative Example 1;
[0034] Fig.10 A schematic diagram of a side scanning electron microscope at 100 μm for an undoped titanium-based tin-antimony-nickel composite coating electrode prepared in Comparative Example 1;
[0035] Fig.11 A schematic diagram of a front scanning electron microscope at 100 μm for an undoped titanium-based tin-antimony-nickel electrode prepared in Comparative Example 2;
[0036] Fig.12 A schematic diagram of a side scanning electron microscope at 100 μm for an undoped titanium-based tin-antimony-nickel electrode prepared in Comparative Example 2;
[0037] Fig.13 This is a comparison chart of real-time detection data of ozone concentration generated when the electrodes of Examples 1-4 and Comparative Examples 1-2 are used for electrocatalytic preparation of ozone;
[0038] Fig.14 The service life of the electrodes of Examples 1-4 and Comparative Examples 1-2 for electrocatalytic production of ozone;
[0039] Fig.15 This is a diagram showing the degradation effect of using the electrode prepared in Example 1 as the anode. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0041] Embodiment 1: A carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode, comprising the following steps:
[0042] 1) First, the surface of a 30x30mm titanium sheet was polished smooth with sandpaper, and then treated with a 15wt% sodium hydroxide solution, and degreased in an 80°C constant temperature oil bath for 60min. After that, the residual alkali solution on the surface was rinsed with deionized water, and then the titanium sheet was placed in a 15wt% oxalic acid solution, and treated in an 80°C constant temperature oil bath for 60min to etch the surface, and finally the surface was rinsed with deionized water.
[0043] 2) Preparation of electrodeposition solution: choline chloride and ethylene glycol were mixed in a molar ratio of 1:2, heated and stirred at 100°C for 20 min to form a colorless transparent solution, then 80 ml of the solution was measured, 4 g of stannous chloride, 450 mg of antimony trichloride and 20 mg of carbon nanotube powder were added thereto, and heated and stirred at 100°C for 20 min to form a uniform mixed solution to obtain an electrodeposition solution.
[0044] 3) The titanium sheet obtained in step 1) was used as a cathode and placed between two parallel graphite electrodes of 35 x 35 mm. Both electrodes were immersed in the electrodeposition solution for pulse electrodeposition. The average current density was constant at 15 mA / cm 2 , frequency is 10HZ, duty cycle is 50%, and electrodeposition is carried out at a constant temperature of 80℃ for 30min.
[0045] 4) The titanium sheet after pulse electrodeposition was placed in an oven at 120° C. to dry for 5 h, and then placed in a muffle furnace and calcined at 600° C. for 1 h. After the calcination, an intermediate layer was obtained.
[0046] 5) Preparation of quenching solution: Add 6 g of stannous oxalate, 450 mg of antimony trichloride and 50 mg of nickel acetate to 60 mL of isopropanol and ultrasonicate for 20 min to form a homogeneous solution.
[0047] 6) The titanium sheet obtained in step 4) is placed in a muffle furnace at 600°C for 10 minutes, and then the titanium sheet is taken out of the muffle furnace and immediately placed in a quenching liquid for cooling. The titanium sheet is immersed in the quenching liquid for 1 minute and then placed in a muffle furnace at 600°C for calcination again. The above steps are repeated 10 times, and the last calcination time is extended to 1 hour to obtain a carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode.
[0048] The front and side scanning electron microscope schematic diagrams of the carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode obtained in Example 1 at 100 μm are shown in FIG. Figure 1 and Figure 2 As shown in the figure, the electrode surface is uneven, full of wrinkles, and has a few cracks. The entire coating fully covers the electrode surface, and the coating thickness is between 15 and 50 μm.
[0049] Embodiment 2: A titanium-based tin-antimony-nickel composite coating electrode doped with conductive carbon black, comprising the following steps:
[0050] 1) First, the surface of a 25x25mm titanium sheet was polished smooth with sandpaper, then treated with a 10wt% sodium hydroxide solution, degreased in a 90°C constant temperature oil bath for 45min, and then rinsed with deionized water to remove the residual alkali solution on the surface. Then, the titanium sheet was placed in a 10wt% oxalic acid solution, treated in a 90°C constant temperature oil bath for 60min to etch the surface, and finally rinsed with deionized water.
[0051] 2) Preparation of electrodeposition solution: choline chloride and ethylene glycol were mixed in a molar ratio of 1:3, heated and stirred at 90°C for 20 min to form a colorless transparent solution, then 40 ml of the solution was measured, 3.5 g of tin tetrachloride, 228 mg of antimony trichloride and 6 mg of conductive carbon black powder were added thereto, and heated and stirred at 90°C for 20 min to form a uniform mixed solution to obtain an electrodeposition solution.
[0052] 3) The titanium sheet obtained in step 1) was used as a cathode and placed between two parallel graphite electrodes of 30x30 mm. Both electrodes were immersed in the electrodeposition solution for pulse electrodeposition. The average current density was constant at 10 mA / cm 2 , frequency is 20HZ, duty cycle is 60%, and electrodeposition is carried out at a constant temperature of 90℃ for 40min.
[0053] 4) The titanium sheet after pulse electrodeposition was placed in an oven at 140° C. to dry for 6 hours, and then placed in a muffle furnace and calcined at 550° C. for 1 hour to obtain an intermediate layer.
[0054] 5) Preparation of quenching solution: Add 4 g of stannous chloride, 171 mg of antimony trichloride and 48 mg of nickel chloride to 40 mL of isopropanol and ultrasonicate for 20 min to form a homogeneous solution.
[0055] 6) The titanium sheet obtained in step 4) is placed in a muffle furnace at 550°C and roasted for 10 minutes, and then the titanium sheet is taken out of the muffle furnace and immediately placed in a quenching liquid for cooling. The titanium sheet is immersed in the quenching liquid for 1 minute and then placed in a muffle furnace at 550°C for roasting again. The above steps are repeated 12 times, and the last roasting time is extended to 2 hours to obtain a titanium-based tin-antimony-nickel composite coating electrode doped with conductive carbon black.
[0056] The front and side scanning electron microscope schematic diagrams of the conductive carbon black-doped titanium-based tin-antimony-nickel composite coating electrode obtained in Example 2 at 100 μm are shown as follows: Figure 3 and Figure 4 As shown, the electrode surface has wrinkles but basically no cracks, and the coating covers the electrode surface with a thickness ranging from 17 μm to 30 μm.
[0057] Embodiment 3: A carbon fiber-doped titanium-based tin-antimony-nickel composite coating electrode, comprising the following steps:
[0058] 1) First, the surface of a 20x20mm titanium sheet was polished smooth with sandpaper, and then the titanium sheet was treated with a 20wt% sodium hydroxide solution, and degreased in a 90℃ constant temperature oil bath for 30min. After that, the residual alkali solution on the surface was rinsed with deionized water, and then the titanium sheet was placed in a 20wt% oxalic acid solution, and treated in a 90℃ constant temperature oil bath for 80min to etch the surface, and finally the surface was rinsed with deionized water.
[0059] 2) Preparation of electrodeposition solution: choline chloride and ethylene glycol were mixed in a molar ratio of 1:4, heated and stirred at 100°C for 20 minutes to form a colorless transparent solution, then 40 ml of the solution was measured, 2 mg of stannous chloride, 171 mg of antimony trichloride and 9 mg of carbon fiber powder were added thereto, and heated and stirred at 100°C for 15 minutes to form a uniform mixed solution to obtain an electrodeposition solution.
[0060] 3) The titanium sheet obtained in step 1) was used as a cathode and placed between two parallel graphite electrodes of 25 x 25 mm. Both electrodes were immersed in the electrodeposition solution for pulse electrodeposition. The average current density was constant at 20 mA / cm 2 , frequency is 20HZ, duty cycle is 40%, and electrodeposition is carried out at a constant temperature of 70℃ for 20min.
[0061] 4) The titanium sheet after pulse electrodeposition was placed in an oven at 120° C. to dry for 5 h, and then placed in a muffle furnace and calcined at 500° C. for 2 h. After the calcination, an intermediate layer was obtained.
[0062] 5) Preparation of quenching solution: Add 5 g of tin tetrachloride, 114 mg of antimony trichloride and 50 mg of nickel chloride to 40 mL of isopropanol and ultrasonicate for 20 min to form a homogeneous solution.
[0063] 6) The titanium sheet obtained in step 4) is placed in a muffle furnace at 500°C for 10 minutes, and then the titanium sheet is taken out of the muffle furnace and immediately placed in a quenching liquid for cooling. The titanium sheet is immersed in the quenching liquid for 1 minute and then placed in a muffle furnace at 500°C for calcination again. The above steps are repeated 15 times, and the last calcination time is extended to 4 hours to obtain a carbon fiber-doped titanium-based tin-antimony-nickel composite coating electrode.
[0064] The front and side scanning electron microscope schematic diagrams of the carbon fiber doped titanium-based tin-antimony-nickel composite coating electrode obtained in Example 3 at 100 μm are shown in FIG. Figure 5 and Figure 6 As shown, the electrode surface is full of wrinkles and unevenness, the coating fully covers the electrode surface, the thickness of the coating is between 25 and 50 μm, and it can be clearly seen that there are two layers of catalyst on the surface of the titanium sheet.
[0065] Embodiment 4: A diamond-doped titanium-based tin-antimony-nickel composite coating electrode, comprising the following steps:
[0066] 1) First, the surface of a 20x10mm titanium sheet was polished smooth with sandpaper, and then the titanium sheet was treated with a 15wt% sodium hydroxide solution, and degreased in an 80°C constant temperature oil bath for 60min. After that, the residual alkali solution on the surface was rinsed with deionized water, and then the titanium sheet was placed in a 15wt% oxalic acid solution, and the surface was etched in an 80°C constant temperature oil bath for 60min, and finally the surface was rinsed with deionized water.
[0067] 2) Preparation of electrodeposition solution: choline chloride and ethylene glycol were mixed in a molar ratio of 1:4, heated and stirred at 90°C for 20 minutes to form a colorless transparent solution, then 40 ml of the solution was measured, 5 mg of tin tetrachloride, 400 mg of antimony trichloride and 15 mg of diamond powder were added thereto, and heated and stirred at 90°C for 15 minutes to form a uniform mixed solution to obtain an electrodeposition solution.
[0068] 3) The titanium sheet obtained in step 1) was used as a cathode and placed between two parallel graphite electrodes of 25 x 25 mm. Both electrodes were immersed in the electrodeposition solution for pulse electrodeposition. The average current density was constant at 25 mA / cm 2 , frequency is 5HZ, duty cycle is 45%, and electrodeposition is carried out at a constant temperature of 60℃ for 20min.
[0069] 4) The titanium sheet after pulse electrodeposition was placed in an oven at 150° C. to dry for 4 hours, and then placed in a muffle furnace and calcined at 450° C. for 3 hours to obtain an intermediate layer.
[0070] 5) Preparation of quenching solution: Add 4 g of stannous oxalate, 200 mg of antimony trichloride and 30 mg of nickel sulfate to 40 mL of isopropanol and ultrasonicate for 20 min to form a homogeneous solution.
[0071] 6) The titanium sheet obtained in step 4) is placed in a muffle furnace at 450°C and roasted for 10 minutes, and then the titanium sheet is taken out of the muffle furnace and immediately placed in a quenching liquid for cooling. The titanium sheet is immersed in the quenching liquid for 1 minute and then placed in a muffle furnace at 450°C for roasting again. The above steps are repeated 15 times, and the last roasting time is extended to 5 hours to obtain a diamond-doped titanium-based tin-antimony-nickel composite coating electrode.
[0072] The front and side scanning electron microscope schematic diagrams of the diamond-doped titanium-based tin-antimony-nickel composite coating electrode obtained in Example 4 at 100 μm are shown in FIG. Figure 7 and Figure 8 As shown, the electrode surface has fewer wrinkles and cracks and is relatively smooth. The coating fully covers the electrode surface, and the thickness of the coating is about 16 μm.
[0073] Comparative Example 1: An undoped titanium-based tin-antimony-nickel composite coating electrode, comprising the following steps:
[0074] The electrode preparation process of Comparative Example 1 repeats that of Example 1, except that no carbon material is added to the electrodeposition solution in step 2), and the remaining steps remain unchanged.
[0075] The front and side scanning electron microscope diagrams of the undoped titanium-based tin-antimony-nickel composite coating electrode obtained in Comparative Example 1 at 100 μm are shown in FIG. Fig. 9 and Fig.10 As shown, the electrode surface is covered with wrinkles and cracks, the coating fully covers the electrode surface, and the thickness of the coating is about 16 μm.
[0076] Comparative Example 2: A titanium-based tin-antimony-nickel electrode comprising the following steps:
[0077] The electrode preparation process of Comparative Example 2 repeats Example 1, except that no carbon material is added to the electrodeposition solution in step 2), and there are no operating steps of step 5) and step 6), and the other conditions remain unchanged.
[0078] The front and side scanning electron microscope diagrams of the undoped titanium-based tin-antimony-nickel composite coating electrode obtained in Comparative Example 2 at 100 μm are shown in FIG. Fig.11 and Fig.12 As shown, the electrode surface is covered with wrinkles and cracks, the coating fully covers the electrode surface, and the thickness of the coating is about 16 μm.
[0079] The electrodes of Examples 1-4 and Comparative Examples 1-2 are used to electrolyze water to produce ozone:
[0080] The voltage and current are controlled by a constant current meter, and a double electrode system is used to carry out the reaction in an electrolytic cell, and the electrolyte is a 0.5M sulfuric acid aqueous solution. The anode is a composite coating electrode prepared in Example 1-4 of the present invention or Comparative Example 1-2, and the cathode is a platinum electrode. The gas outlet on the anode side of the electrolytic cell is connected to an ozone detector to detect the generation of ozone in real time. During the electrocatalytic ozone production reaction, the current density is controlled at 250mA / cm 2 , the cell voltage is controlled between 3-10V, and the reaction time is 20min. Fig.13 It can be found that as the reaction proceeds, the ozone concentration generated by Examples 1-4 and Comparative Example 1 increases rapidly, and basically reaches equilibrium within 3 minutes. After running for 20 minutes, the ozone concentration generated by the electrode doped with carbon material is between 650ppm and 700ppm, and the ozone concentration generated by the electrode not doped with carbon material is about 550ppm, and the concentration difference reaches more than 100ppm. It can be seen that the performance of the electrode doped with carbon material for the preparation of ozone by electrolysis of water is improved.
[0081] In order to verify the stability of the prepared electrode, an accelerated life test was carried out with the composite electrode as the anode and the platinum electrode as the cathode. The current density was controlled at 250 mA / cm 2 , the electrolyte is 0.5M sulfuric acid, and the voltage exceeds 10V, it is considered that the electrode has reached the life limit. Fig.14 It can be found that the addition of carbon material has a better stability on the life of the electrode. The material prepared in Example 1 has better stability (the voltage rises slowly within 40 hours of the life test and is deactivated after 67 hours), and has good industrial application prospects.
[0082] Figure 13-14 The carbon nanotube-doped, conductive carbon black-doped, carbon fiber-doped, diamond-doped, undoped, and undoped and single-layer electrodes correspond to the electrodes of Examples 1-4 and Comparative Examples 1-2, respectively.
[0083] The electrocatalytic performance and service life of the carbon material-doped titanium-based tin-antimony-nickel composite coating electrode of the present invention have been significantly improved compared with the prior art. For example, the existing literature "Simultaneous ozone and hydrogen peroxide electrosynthesis via defect modulation in Ni,Sb-doped SnO 2 Electrocatalysts” Figure 3 Figure 1 discloses Imp-Ni-Sb-SnO 2 The electrode is at 250 mA / cm 2 The results of the long-term stability test showed that the electrocatalyst was deactivated after 37 hours, and the electrocatalytic life was significantly shorter than that of the electrodes of Examples 1-4 of the present invention.
[0084] The carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode of Example 1 is used to degrade organic pollutants:
[0085] The electrolyte is 400 mL of 0.05 M sodium sulfate aqueous solution, and the concentration of organic pollutants in the solution is 10 mg / L (the type of organic pollutants is shown in Fig.15 ), the current density is constant at 100 mA / cm 2 , using the carbon nanotube-doped titanium-based tin-antimony-nickel composite coating electrode of Example 1 as the anode and a smooth and clean stainless steel sheet as the cathode, an electric reactor was built for electrochemical degradation, and samples were taken every 4 minutes for a total of 20 minutes. The samples were tested by liquid chromatography, and the concentration of organic pollutants was determined based on the peak area. Fig.15 It can be found that all tested organic pollutants were completely degraded within 20 minutes, which proves the high-efficiency ozone production capacity and industrial application potential of the composite coating catalyst.
[0086] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode, characterized in that The following steps are involved: 1) Titanium sheet pretreatment: The titanium sheet is subjected to surface grinding, alkali washing and acid treatment in sequence; 2) Preparation of active intermediate layer: placing the titanium sheet treated in step 1) in an electrodeposition solution for constant temperature pulse electrodeposition, wherein the electrodeposition solution is a mixture containing a tin source, an antimony source and a carbon material powder, drying after electrodeposition, and then calcining in a muffle furnace to grow an intermediate layer doped with a carbon material on the titanium sheet; 3) Cyclic thermal oxidation and quenching treatment: Step 2) After the sintered titanium sheet is taken out of the muffle furnace, it is immediately immersed in a quenching liquid containing a tin source, an antimony source and a nickel source while it is still hot for quenching treatment, and then placed in a high-temperature muffle furnace for sintering again for thermal oxidation treatment. The above quenching and thermal oxidation steps are repeated for multiple cycles to obtain a titanium-based tin-antimony-nickel metal oxide composite coating electrode.
2. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that The alkaline washing process in step 1) is: degreasing in a 10-40wt% sodium hydroxide solution for 30-90min, the temperature of the solution is controlled between 50-100°C, and then the residual alkaline solution on the surface is rinsed with deionized water; the acid washing process is: etching in a 10-40wt% oxalic acid solution for 60-120min, the temperature of the solution is controlled between 50-100°C, and then the residual acid solution on the surface is rinsed with deionized water.
3. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that Step 2) The preparation process of the electrodeposition solution is as follows: choline chloride and ethylene glycol are mixed, the molar ratio of choline chloride to ethylene glycol is 1:1-10, heated and stirred in a constant temperature oil bath until a colorless solution is formed, the oil bath temperature range is 50-100°C, and then a tin source, an antimony source and a carbon material are added to the solution, and stirred to form a uniform dispersion.
4. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that In step 2), in the electrodeposition solution, the tin source is at least one of tin tetrachloride, stannous oxalate, and stannous chloride, the antimony source is antimony trichloride, and the carbon material powder is at least one of carbon fiber, diamond, graphene, conductive carbon black, and carbon nanotubes; in the electrodeposition solution of step 2), the tin source concentration is 0.1-1M, the antimony trichloride concentration is 0.01-0.1M, and the carbon material concentration is 0.1-1g / L.
5. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that The electrodeposition in step 2) adopts a three-electrode system, with the treated titanium sheet as the cathode, and two anodes with an area larger than the titanium sheet are placed in parallel on both sides of the cathode. The cathode and the anode are immersed in the electrodeposition solution for pulse electrodeposition reaction. The anode is at least one of a graphite electrode, a platinum sheet electrode, and an iridium tantalum titanium electrode, and the size of the anode is 1.2-3.5 times the size of the cathode.
6. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that Step 2) The average current density of pulse electrodeposition is 5-50mA / cm 2 , preferably 10-25 mA / cm 2 , frequency is 0.1-100HZ, preferably 5-20HZ, duty cycle is 10-90%, preferably 40-60%, deposition temperature is 50-100℃, preferably 60-90℃, electrodeposition time is 10-40min, preferably 20-40min; after pulse electrodeposition, the titanium sheet is placed in an oven for drying, and then placed in a muffle furnace for calcination, the oven drying temperature is 80-160℃, preferably 100-140℃, the drying time is 5-10h, the muffle furnace calcination temperature is 400-700℃, preferably 450-600℃, and the calcination time is 1-5h.
7. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that Step 3) the quenching liquid uses isopropanol as solvent, the tin source concentration in the quenching liquid is 0.1-1 M, the antimony source concentration is 0.01-0.1 M, the nickel source concentration is 1-10 mM, the tin source is at least one of tin tetrachloride, stannous oxalate, and stannous chloride, the antimony source is antimony trichloride, and the nickel source is at least one of nickel chloride, nickel acetate, nickel sulfate, and nickel carbonate.
8. The method for preparing a carbon material doped titanium-based tin-antimony-nickel composite coating electrode according to claim 1, characterized in that Step 3) In the process of cyclic thermal oxidation and quenching treatment, the roasting temperature range of the muffle furnace is 400-700°C, preferably 450-600°C. After roasting for 5-20 minutes, the titanium sheet is taken out of the muffle furnace and immediately placed in the quenching liquid for cooling. After soaking for 0.5-2 minutes, it is roasted again. The above steps are repeated 5-15 times. After the last soaking in the quenching liquid, the roasting time in the muffle furnace is extended to 1-5 hours.
9. A carbon material-doped titanium-based tin-antimony-nickel composite coating electrode prepared by the method according to any one of claims 1 to 8.
10. Use of a carbon material doped titanium-based tin-antimony-nickel composite coating electrode as claimed in claim 9 in electrochemical preparation of ozone or electrocatalytic degradation of organic pollutants, characterized in that When applied to electrochemical preparation of ozone, a dual-electrode system is used to carry out the reaction in an electrolytic cell, the electrolyte is a 0.01-0.1M sulfuric acid aqueous solution, the carbon material-doped titanium-based tin-antimony-nickel composite coating electrode is used as the anode, and the platinum electrode is used as the cathode to carry out the electrocatalytic ozone production reaction; When applied to the electrocatalytic degradation of organic pollutants, the carbon material-doped titanium-based tin-antimony-nickel composite coating electrode is used as the anode, the stainless steel sheet is used as the cathode, the electrolyte is a 0.01-0.1M sodium sulfate aqueous solution, and the electrolyte contains organic pollutants to perform an electrocatalytic degradation reaction of the organic pollutants.
Citation Information
Cited By
Phosphorus-doped iridium tantalum cerium bifunctional electrode and preparation method and application thereof
CN122214945A
A phosphorus-doped iridium tantalum cerium bifunctional electrode, a preparation method and application thereof
CN122214945B